Objetos de aprendizagem: uma ferramenta pedagógica no processo de ensino aprendizagem do conteúdo de estequiometria na disciplina química no ensino médio - Silva, Lilianne de Sousa (2018)
The Chemistry discipline seeks to provide learning that guarantees students the conditions to understand and develop full awareness of their responsibilities and rights while building the scientific knowledge inherent to the discipline. However, we have the impression that the teaching of this discipline is regarded by most students as being far from the reality in which they are inserted and full of formulas and theories to be decorated. It is necessary to overcome the teaching practice centered on the memorization and reproduction of scientific concepts. In this scenario, the interest of the present study arose in order to evaluate the impact of the use of learning objects on the performance of high school students, in the content of stoichiometry, through an experimental study. This work was theoretically grounded in the works and researches of Taro and Dutra (2007), Santos e Silva (2014), Costa e Zorzi (2008), Silva (2015), Grisolía e Grisolía (2009), and Carneiro and Silveira (2014). Staver and Lumpe (1995), Moran, Masetto and Behrens (2006), Oliveira (2013), Sabbatini (2012), Beck (2002), among others. An experimental research was developed in which we collected quantitative and qualitative data through the application of a Likert scale and a test (pre and post) with students from two classes of the 1st grade of High School. Data analysis revealed that the use of learning objects facilitates the understanding of theoretical terms / concepts and that sometimes are not possible to be visualized by the students. We can say that there is a large gap in the mathematical content needed to understand stoichiometric calculations, thus making it necessary to carry out interdisciplinary practice aiming at the development of fundamental mathematical-logical skills for the content of Chemistry. Based on the results of the tests, for this study group, we can conclude with some certainty that the use of learning objects to teach stoichiometry was efficient and effective, helping to build meaningful learning. We observed that the results go according to our experimental hypothesis, that is, the use of learning objects interferes positively in the teaching-learning of stoichiometry contents. Thus, we can consider that it is necessary to train the teacher to make a more effective use of this tool in the classroom, as well as to contribute to the construction of the student's autonomy in the teaching-learning process